What is the scientific evidence on telecommuting and COVID-19 in the musculoskeletal system: a systematic review (Research, Society and Development, 2023)
This study aims to gather and analyze evidence on the changes of home office work in the musculoskeletal system during the COVID-19 pandemic. This is a systematic review of the literature that was conducted by the Cochrane Handbook for Systematic Reviews of Interventions and reported in accordance with the statement Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA), carried out in the databases PubMed, Scopus, Virtual Health Library (VHL), Web of Science and Science Direct. The research question was: What are the repercussions of telecommuting in the COVID-19 pandemic on the musculoskeletal system? A total of 16 studies were found and after analysis, five studies were included in this work. Among the studies analyzed, it was observed that the repercussions of telecommuting in the COVID-19 pandemic on the musculoskeletal system, its highest occurrences of musculoskeletal symptoms were in the following body regions: pain in the back, neck, shoulder and hands and in females. It suggests that new future studies with a better level of quality of evidence are needed to identify the results and strengthen investigations on the theme involved.